1999
DOI: 10.1002/hep.510300124
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol, a new nonselective beta-blocker with intrinsic anti-alpha1-adrenergic activity, has a greater portal hypotensive effect than propranolol in patients with cirrhosis

Abstract: Only some patients show a substantial hepatic venous pressure gradient (HVPG) reduction after propranolol, which makes it desirable to investigate drugs with greater portal hypotensive effect. The aim of this study was to investigate whether carvedilol, a nonselective beta-blocker with anti-alpha 1-adrenergic activity, may cause a greater HVPG reduction than propranolol. Thirty-five cirrhotic patients had hemodynamic measurements before and after the random administration of carvedilol (n 14), proprano-lol (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
156
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(175 citation statements)
references
References 36 publications
(51 reference statements)
12
156
3
4
Order By: Relevance
“…1 However, the vasodilating activity of carvedilol may enhance arterial hypotension and sodium retention, a risk which is especially relevant in patients with advanced, decompensated cirrhosis. 19,20,21 Drugs that inhibit cytochrome P450 2D6 activity (quinidine, paroxetine, fluoxetine, propafenone) may increase plasma concentrations of R-carvedilol (a stereoisomer with alpha-and beta-adrenergic blocking activity). In contrast, plasma concentrations of S-carvedilol (which has only beta-blocker activity) increase much less.…”
Section: Carvedilolmentioning
confidence: 99%
See 3 more Smart Citations
“…1 However, the vasodilating activity of carvedilol may enhance arterial hypotension and sodium retention, a risk which is especially relevant in patients with advanced, decompensated cirrhosis. 19,20,21 Drugs that inhibit cytochrome P450 2D6 activity (quinidine, paroxetine, fluoxetine, propafenone) may increase plasma concentrations of R-carvedilol (a stereoisomer with alpha-and beta-adrenergic blocking activity). In contrast, plasma concentrations of S-carvedilol (which has only beta-blocker activity) increase much less.…”
Section: Carvedilolmentioning
confidence: 99%
“…In contrast, plasma concentrations of S-carvedilol (which has only beta-blocker activity) increase much less. 19 Thus, these drugs increase the risk of hypotension during carvedilol administration. Patients Carvedilol is a potent nonselective beta-blocker, and as such, it decreases heart rate and cardiac index (blockade of beta-1 adrenergic receptors) and causes splanchnic vasoconstriction (blockade of beta-2 adrenergic receptors), which result in a reduced portal blood flow, and thereby in decreased portal pressure.…”
Section: Carvedilolmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs) reduced cardiac index and MAP resulting in worsened outcomes in patients with advanced cirrhosis and ascites [40][41][42][43] . Finally, other studies of newer-generation beta-blockers such as carvedilol showed that although carvedilol may be more potent than propranolol in terms of reducing portal hypertension, it was associated with more systemic hypotension, increase in plasma volume and body weight, and worsening of preexisting ascites [44][45][46][47] .…”
Section: Blood Pressure and Cirrhosismentioning
confidence: 99%